Pengaruh Metode Kaisa Terhadap Kemampuan Menghafal Surat-Surat Pendek Al-Qur’an Dan Hadits Pada Anak Di Tk Aisyiyah 17 Jasem Ngoro Mojokerto - Try Nur Aliyah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
This study aims (1) to determine the effect of the Kaisa method on the ability to memorize short letters of the Al-Qur'an and hadith in children at TK Aisyiyah 17 Jasem, (2) to determine the influence of the Kaisa method on the ability to memorize short letters. Al-Qur'an and hadith in TK Aisyiyah 17 Jasem. The research method uses quantitative ex-post facto correlation type. The sampling technique used was purposive sampling. Research data collection techniques are questionnaires and documentation. Test the validity of the questionnaire instrument using expert tests (judges). The data analysis technique used the product moment correlation formula. The conclusion of this study is that (1) there is an effect of the Kaisa method on the ability to memorize short letters from the Al-Qur'an and hadith in children. This is evidenced by the results of the calculation of rcount> rtabel, (0.999> 0.602) then H0 is rejected and H1 is accepted, (2) and the magnitude of the influence seen from the calculation results is 0.999 which has been consulted with the correlation coefficient value at the value of 0.800-1.00 including the category high, so it can be interpreted that the influence of the Kaisa method has a major effect on the ability to memorize short letters of the Al-Qur'an and hadiths in children at Aisyiyah 17 Kindergarten Jasem Ngoro Mojokerto.